2016
DOI: 10.1038/srep37925
|View full text |Cite
|
Sign up to set email alerts
|

Kitaev exchange and field-induced quantum spin-liquid states in honeycomb α-RuCl3

Abstract: Large anisotropic exchange in 5d and 4d oxides and halides open the door to new types of magnetic ground states and excitations, inconceivable a decade ago. A prominent case is the Kitaev spin liquid, host of remarkable properties such as protection of quantum information and the emergence of Majorana fermions. Here we discuss the promise for spin-liquid behavior in the 4d5 honeycomb halide α-RuCl3. From advanced electronic-structure calculations, we find that the Kitaev interaction is ferromagnetic, as in 5d5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
328
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(348 citation statements)
references
References 55 publications
19
328
1
Order By: Relevance
“…While indications for a field-induced spin liquid in Heisenberg-Kitaev models were found in numerical simulations in Ref. [19], a full theory is not available. Alternatively, the phase above H c could be adiabatically connected to the high-field limit, and the soft mode would then correspond to a high-field magnon.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…While indications for a field-induced spin liquid in Heisenberg-Kitaev models were found in numerical simulations in Ref. [19], a full theory is not available. Alternatively, the phase above H c could be adiabatically connected to the high-field limit, and the soft mode would then correspond to a high-field magnon.…”
Section: Figmentioning
confidence: 99%
“…Interestingly, NMR measurements with fields in the specific direction H c performed down to 4 K have indicated the formation of a sizable * Corresponding author: a.wolter@ifw-dresden.de spin gap at high fields [30]. Additionally, numerical exactdiagonalization studies of an extended Heisenberg-Kitaev model found hints for a transition from zigzag magnetic ordering to a spin-liquid state when applying a magnetic field [19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We first present data of a crystal measured under 12 T field applied along the c-axis, in which case the T N is less affected by field 22,23,36 . In the paramagnetic phase, nine NMR lines are expected, given one center line and two satellites for each 35 Cl site, and three inequivalent …”
Section: Magnetization Data and Analysismentioning
confidence: 99%
“…15 For example, in α-RuCl 3 (RuCl 3 ), an actively studied KSL candidate, comprehensive ab initio computations and recent dynamical studies 16,17 suggest that ferromagnetic K and antiferromagnetic Γ interactions are dominant and comparable in magnitude, while J is negligible. [18][19][20] The balance of these and additional small further neighbor interactions causes RuCl 3 and other KSL candidates to magnetically order at low temperature; however, it is still unclear whether or not the often-large Γ interaction prefers magnetic ordering. Meanwhile, the community has attempted to revive the possibility of a KSL in RuCl 3 by applying a small magnetic field, with the effect of entering a potential spin liquid phase with no magnetization.…”
Section: Introductionmentioning
confidence: 99%